Gestión administrativa en el GAD Municipal San Francisco de Puebloviejo, período 2023. - Fajardo Alvear, Mercedes Nathaly (2024)
The administrative management in the Municipal Autonomous Decentralized Government (GAD) of San Francisco de Puebloviejo focused on several key aspects that positively impacted local development and the quality of life of citizens, measures were implemented to strengthen transparency and accountability in all administrative activities. This was achieved by digitizing processes, publishing detailed financial information and promoting citizen participation in decision-making. Regarding financial management, efficiency in the use of public resources was prioritized. Periodic internal audits were carried out to guarantee the proper management of municipal funds, and control mechanisms were established to prevent their misuse. In the area of planning and development, a strategic plan was prepared and executed that included projects aimed at improving basic infrastructure, promoting local economic development and promoting environmental sustainability. In addition, we worked in close collaboration with other institutions and organizations to maximize the impact of the implemented initiatives. Human talent management was another relevant aspect during the aforementioned period. Actions were carried out to strengthen the capabilities of municipal personnel through training and training programs, with the aim of improving the provision of public services and promoting a favorable work environment.